Individual versus group exercise effect on youth physical activity levels: a randomised controlled trial - Rockli Kim; S V Subramanian; Dario Novak; Marko Čule; Jinseo Kim (BMJ Open Sport & Exercise Medicine)
Objectives To explore the effects of two different types of exercise (individual vs group) on physical activity (PA) among Croatian university students.Methods A total of 976 university students between the ages of 19 and 20 years (age 19.4±1.1 years, body mass index 21.9±2.9 kg/m2) were randomly assigned to either the control group (individual exercise) (n=504) or the intervention group, which received group exercise (n=472). Pre- and postintervention measures included: self-rated health, parents’ occupation, psychological distress, nutritional status and PA levels. The overall intervention effect was estimated using linear regression method, and heterogeneity in intervention effect was assessed by modelling complex variance.Results Group-based exercise intervention significantly increased total PA time by more than 10 metabolic equivalents (METS) hours per week compared with individual-based exercise control group. When considering different types of activities, the intervention effect was stronger for vigorous activity (increase by almost 6 METS hours per week) than walking activity (2.5 METS hours per week). The change in moderate activity level was not significant after covariate adjustment. In addition, intervention was also effective in reducing sedentary hours. Finally, when complex level-1 heterogeneity was modelled by intervention status, we found substantially larger variance in the intervention group compared with the controls, indicating presence of heterogeneous treatment effect.Conclusions This study discusses major implications of different ways of exercising among youths from a health, educational and sport perspective. Intervention and policies that leverage school social capital might serve as an avenue for health promotion in youth.